Bunch yield response of two cultivars of plantain (Musa spp., AAB, Subgroups French and False horn) to hot water treatment and fertilizer application planted after forest and bush/grass fallow - Hauser, S.; Mekoa, C.; Jacobsen, K.S. (Informa UK Limited, 2008)
Effects of fallow type, sucker sanitation (hot-water treatment, HWT) and fertilizer application on yield, root and corm health of two plantain cultivars were investigated. Most yield parameters were strongest affected by fallow type with more producing plants, higher bunch mass and yield after forest clearing than in bush/grass fallow. The second most important factor was HWT with more producing plants (52.3%) than in control (35.8%, p 5 0.0001). Fertilizer application increased the proportion of producing plants by 9%, p 5 0.018 and yield from 4.08–5.79 Mg ha71. Combined HWT and fertilizer had strong synergistic effects. Cultivar interacted with fallow and HWT: in bush/grass fallow yield did not differ between cultivars (2.17 Mg ha71); in forest fallow Essong produced 57% (9.4 Mg ha71) more than Ebang (6.0 Mg ha71, p 5 0.001). Essong yielded 65% more after HWT than Ebang (8.0 versus 4.9 Mg ha71, p 5 0.001), yet not when untreated. A limited sink capacity of Ebang is likely to constrain yield increases. HWT improved root and corm health and was better in forest than in bush/grass land. In bush/grass fallow no treatment attained yields as high as in forest even when untreated and not fertilized. Soil chemical properties were not correlated with yield.